2021
DOI: 10.1038/s41598-021-96496-0
|View full text |Cite
|
Sign up to set email alerts
|

3D printing fluorescent material with tunable optical properties

Abstract: The 3D printing of fluorescent materials could help develop, validate, and translate imaging technologies, including systems for fluorescence-guided surgery. Despite advances in 3D printing techniques for optical targets, no comprehensive method has been demonstrated for the simultaneous incorporation of fluorophores and fine-tuning of absorption and scattering properties. Here, we introduce a photopolymer-based 3D printing method for manufacturing fluorescent material with tunable optical properties. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 32 publications
(59 reference statements)
0
22
1
Order By: Relevance
“…Overall, the investigations on Lumogen phantoms indicate a genuine photostability, making such phantoms well-suited for performance monitoring, device comparison, and maintenance of hand imagers. In contrast, our stability investigations on phantoms printed with ICG do not confirm the high stability over time reported by Ruiz et al 36 These authors observed deviations between þ4% and −4% (with 1% to 2% error bars) over 2 months without a systematic tendency. Possible reasons are the different base resin, the different printer types, and differences in the UV curing process.…”
Section: Photostability and Bleachingcontrasting
confidence: 99%
See 2 more Smart Citations
“…Overall, the investigations on Lumogen phantoms indicate a genuine photostability, making such phantoms well-suited for performance monitoring, device comparison, and maintenance of hand imagers. In contrast, our stability investigations on phantoms printed with ICG do not confirm the high stability over time reported by Ruiz et al 36 These authors observed deviations between þ4% and −4% (with 1% to 2% error bars) over 2 months without a systematic tendency. Possible reasons are the different base resin, the different printer types, and differences in the UV curing process.…”
Section: Photostability and Bleachingcontrasting
confidence: 99%
“…It is well known that ICG stability is very sensitive against environmental factors. Surprisingly, Ruiz et al 35,36 explained the stability of their phantoms by differences in the chemical structure between the applied "laser dye" (IR-125) and ICG, although the data sheet of the manufacturer (Exciton Inc., Lockburne, Ohio, United States) explicitly declares that IR-125 and ICG are two names for the same substance (CAS Registry Number: 3599-32-4). 46 Our direct comparison of Lumogen and ICG phantoms illustrates that Lumogen behaves much more stable, which is in accordance with the known differences in stability between rylene and cyanine dyes.…”
Section: Photostability and Bleachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Serial dilutions of fluorescent contrast agents can be prepared with tissue optical properties and used for system characterization; however, this method is prone to inter-user reproducibility errors, short shelf-life, and may require a dedicated preparation space to satisfy environmental hazard requirements. Solid composite phantoms provide the opportunity for extended shelf stability and multi-center distribution [ 14 , 15 ]. A solid standardization reference phantom was proposed in 2016 and has been subsequently revised in recent years [ 6 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This concept was extended in 2020 with a modular design to address manufacturability and utilized an ICG-equivalent fluorophore in place of quantum dots [ 14 ]. To further address design flexibility, a resin-based 3D printing technique was developed [ 15 ]. While the primary focus of many of the solid composite reference phantoms have been to provide engineers with detailed system characterization, 3D printing provides the ability to manufacture more complex shapes with controlled, homogeneous optical properties.…”
Section: Introductionmentioning
confidence: 99%